High-performance liquid chromatographic separation of unusual β(3)-amino acid enantiomers in different chromatographic modes on Cinchona alkaloid-based zwitterionic chiral stationary phases - Ilisz, István; Grecsó, Nóra; Papoušek, Roman; Pataj, Zoltán; Barták, Petr; Lázár, László; Fülöp, Ferenc; Lindner, Wolfgang; Péter, Antal (Amino acids, 2015)
Polar-ionic and hydro-organic mobile phase mode of high-performance liquid chromatographic separations of 23 sterically constrained primary β(3)-amino acid enantiomers containing, alkyl, aryl or heteroaryl side-chains were carried out by using newly developed Cinchona alkaloid-based zwitterionic chiral selectors and the stationary phases Chiralpak ZWIX(+)™ and ZWIX(-)™. In the polar-ionic mode, the effects of the composition of the bulk solvent and the natures of the co- and counter-ions, while in the hydro-organic mode, the effects of the pH, the counter-ion concentration and the structures of the analytes were investigated. The separations of the enantiomers of these 23 primary β(3)-amino acids, which can be classified as a series of quasi- (pseudo-) homologs, were optimized in both chromatographic modes. The elution sequence was determined in most cases and a reversal of elution order on ZWIX(+)™ and ZWIX(-)™ column was observed. On the basis of this intermolecular recognition model between the selectors and the given enantiomers an indirect assignment of the resolved enantiomer via chromatography is proposed.
Keywords: modely kardiovaskulární; vysokoúčinná kapalinová chromatografie; chininové alkaloidy; Amino Acids; Chromatography, High Pressure Liquid; Cinchona Alkaloids; Models, Cardiovascular; aminokyseliny